2009
DOI: 10.1007/s00248-009-9555-3
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Transformations and Diversity of Ammonia-Oxidizing Bacteria in a Desert Ephemeral Stream Receiving Untreated Wastewater

Abstract: Levels of inorganic nitrogen species (ammonia, nitrite, and nitrate), ammonia oxidation potential (AOP), and diversity of ammonia-oxidizing bacteria (AOB) were studied in the sediments of a 50-km-long segment of an ephemeral stream in the Negev desert, receiving untreated wastewater. Water analysis in downstream sampling points showed reductions of 91.7% in biological oxygen demand, 87.7% in chemical oxygen demand, 73.9% in total nitrogen, and 72.8% in total ammonia nitrogen. Significant AOP levels in the sedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 41 publications
1
11
0
1
Order By: Relevance
“…Phylogenetic analysis of bacterial amoA gene sequences suggested that AOB was dominated by Nitrosospira-like sequences, with Nitrosomonas-like sequences minimum. AOB cluster-3 was found in all the samples, which was in consistent with previous reports Shen et al 2008;Angel et al 2010;Liu et al 2010). The presence of Nitrosomonas-like sequences could be possibly due to higher ammonium concentration in R2 and R3 soils (Webster et al 2002).…”
Section: Community Structure Of Aobsupporting
confidence: 92%
“…Phylogenetic analysis of bacterial amoA gene sequences suggested that AOB was dominated by Nitrosospira-like sequences, with Nitrosomonas-like sequences minimum. AOB cluster-3 was found in all the samples, which was in consistent with previous reports Shen et al 2008;Angel et al 2010;Liu et al 2010). The presence of Nitrosomonas-like sequences could be possibly due to higher ammonium concentration in R2 and R3 soils (Webster et al 2002).…”
Section: Community Structure Of Aobsupporting
confidence: 92%
“…; sequences – and ). The results are in line with previous studies showing that cluster 3 of Nitrosospira dominates desert soils (Nejidat, ; Angel et al ., ; Orlando et al ., ). Together, the results suggest that arid conditions have selected for a limited AOB diversity compared with temperate climates (e.g.…”
Section: Resultsmentioning
confidence: 98%
“…An initial benthic microbial seed was obtained in March 2009 from the Habsor Stream, Israel (Angel et al ., ). The biofilm was scraped off the stream bed material, mixed into 3 l of mineral nutrient solution, filtered through a 75‐µm mesh to remove large grazers and particles and spread evenly over the flume.…”
Section: Methodsmentioning
confidence: 99%
“…The major parameters affecting nitrification in stream ecosystems are NH 4 + and oxygen concentrations, concentrations and nature of organic matter, pH, temperature, diversity and abundance of nitrifiers, stream morphology, concentrations of other chemical elements (such as phosphorous) and, of particular relevance to this study, overlying water velocity (Prinčič et al ., ; Butturini et al ., ; Wollheim et al ., ; Kemp and Dodds, ; Webster et al ., ; Gücker and Boëchat, ; Angel et al ., ). The importance of relating NH 4 + uptake processes (assimilation, nitrification and denitrification) to flow conditions derives from the reliance of these processes on the transfer of key solutes from the bulk water to the benthic biofilms.…”
Section: Introductionmentioning
confidence: 97%